Fermionic entanglement in the presence of background electric and magnetic fields - Shagun Kaushal (European Physical Journal C: Particles and Fields)
Abstract In this study, we investigate the fermionic Schwinger effect in the presence of a constant magnetic field within $$(1+3)$$ ( 1 + 3 ) -dimensional Minkowski spacetime, considering both constant and pulsed electric fields. We analyze the correlations between Schwinger pairs for the vacuum and maximally entangled states of two fermionic fields. The correlations are quantified using entanglement entropy and Bell’s inequality violation for the vacuum state, while Bell’s inequality violation and mutual information are used for the maximally entangled state. One can observe the variation of the entanglement produced for fermionic modes with respect to different parameters. Additionally, we discuss the key differences from the behaviour of scalar fields in this context. This study offers deeper insights into quantum field theory and the dynamics of entanglement in the fermionic Schwinger effect.